Prediction of return with the minimum variance zero-beta portfolio - Morgan, I.G. (Journal of Financial Economics, 1975)
This paper tests prediction of returns on stocks using a direct estimate of the minimum variance zero beta portfolio z. The composition of this portfolio is implicit in Black's paper on capital market equilibrium in the absence of riskless borrowing or lending. Portfolios of stocks drawn from the same industries are used to estimate z. The predictions of Black's equilibrium return equation are compared with those of cross-sectional regressions of return on risk.